Bis(dicyanamido-κN)[tris(3-aminopropyl)amine-κ(4) N]nickel(II) - Luo, Jun (International Union of Crystallography, 2013)
In the title complex, [Ni(C(2)N(3))(2)(C(9)H(24)N(4))], the Ni(II) atom is coordinated in a distorted octahedral geometry by one tris(3-aminopropyl)amine (trisapa) ligand and two dicyanamide (dca) ligands [one of them disordered in a 0.681 (19):0319 (19) ratio]. Intermolecular N—H⋯N hydrogen bonds involving the N atoms of the dca anions and the trisapa amine H atoms result in the formation of a three-dimensional network.